2012
DOI: 10.1371/journal.pbio.1001319
|View full text |Cite
|
Sign up to set email alerts
|

Competing Sound Sources Reveal Spatial Effects in Cortical Processing

Abstract: Neurons in the avian auditory forebrain show strong sensitivity to the spatial configuration of two competing sources, even though there is only weak spatial dependence for any single source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(75 citation statements)
references
References 35 publications
6
69
0
Order By: Relevance
“…Importantly, our stimuli were two spectro-temporally complex stimuli chosen so that their various components would strongly bind to one of two perceptual objects. Similarly, in the work in avian field-L discussed above, spatial modulation of song identity was the dependent variable (Maddox et al 2012). In the cat, it was the preferential tuning to one of two concurrent streams of rhythmic stimuli that was modulated by their relative location (Middlebrooks and Bremen 2013).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Importantly, our stimuli were two spectro-temporally complex stimuli chosen so that their various components would strongly bind to one of two perceptual objects. Similarly, in the work in avian field-L discussed above, spatial modulation of song identity was the dependent variable (Maddox et al 2012). In the cat, it was the preferential tuning to one of two concurrent streams of rhythmic stimuli that was modulated by their relative location (Middlebrooks and Bremen 2013).…”
Section: Discussionmentioning
confidence: 97%
“…The picture appears to be very different using multiple, concurrent complex stimuli and various information-based approaches to analyze single-unit responses. For instance, in the avian field-L (homologue of the auditory cortex), song identification is strongly modulated by the relative location of a concurrent masker (Maddox et al 2012). At a population level, the resulting spatial unmasking of the target approaches what can be demonstrated behaviorally (Best et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…First, we found that the auditory telencephalon of zebra finches responds preferentially to stimulation from the contralateral auditory hemifield. This is consistent with: 1) Findings in L2 of head-fixed non-songbirds hearing sounds (owls (Cohen & Knudsen, 1998), chicks (Scheich, 1983), and doves (Biederman-Thorson, 1970)); 2) the ascending auditory pathway in zebra finches which shows a predominantly contralateral projection from the brain stem nuclei to the midbrain and ipsilateral from there to the forebrain (Wild, Krützfeldt, & Kubke, 2010); 3) reduction in contralateral hearing-induced EGR-1 expression response after plugging one ear during song playback (Feenders et al, 2008); and 4) the improved ability to distinguish a target from a masking stimulus if the target is presented on the contralateral side and the masker on the ipsilateral side compared to the opposite scenario (Maddox, Billimoria, Perrone, Shinn-Cunningham, & Sen, 2012). It is also similar to the mammalian auditory system (Glendenning, Baker, Hutson, & Masterton, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In nature, these different sounds can come from spatially separated sources and spatial information could thus be used to further enhance discrimination (Bee, 2008;Dent et al, 2009;Maddox et al, 2012). A full recognition task in the natural context might also combine the tasks of discriminating one particular individual and determining its spatial location, i.e.…”
Section: Research Articlementioning
confidence: 99%